Polymicrobial interaction between Lactobacillus and Saccharomyces cerevisiae: coexistence-relevant mechanisms. (4th May 2021) - Xu, Zhenbo; Lu, Zerong; Soteyome, Thanapop; Ye, Yanrui; Huang, Tengyi; Liu, Junyan; Harro, Janette M.; Kjellerup, Birthe V.; Peters, Brian M.
Abstract: The coordination of single or multiple microorganisms are required for the manufacture of traditional fermented foods, improving the flavour and nutrition of the food materials. However, both the additional economic benefits and safety concerns have been raised by microbiotas in fermented products. Among the fermented products, Lactobacillus and Saccharomyces cerevisiae are one of the stable microbiotas, suggesting their interaction is mediated by coexistence-relevant mechanisms and prevent to be excluded by other microbial species. Thus, aiming to guide the manufacture of fermented foods, this review will focus on interactions of coexistence-relevant mechanisms between Lactobacillus and S. cerevisiae, including metabolites communications, aggregation, and polymicrobial biofilm. Also, the molecular regulatory network of the coexistence-relevant mechanisms is discussed according to omics researches.